Perlindungan Hukum Bagi Petani Terdaftar Penerima KUR Pada Kasus KUR TANI Fiktif Di Kabupaten Lombok Timur - Zahara, Annisa; Wardani, Nizia Kusuma (Bagian Hukum Bisnis Fakultas Hukum Universitas Mataram, 2024)
The distributor of Farmer's People's Business Credit (KUR TANI). Thisresearch uses a type of normative research with a statutory approach method(Statute Approach), conceptual approach (Conceptual Approach), and caseapproach method (Case Approach) to describe the problem. Based on the resultsof the research and discussion, it was concluded that the forms of legal protectionfor registered farmers who receive KUR are divided into 2 (two), namelypreventive legal protection and repressive legal protection, and the provision ofsanctions or legal responsibility can be in the form of administrative sanctions,civil sanctions, and criminal sanctions. The procedure that farmers can carry outif their data is misused is to resolve disputes through litigation.Keywords: Credit; Fictitious; Legal protection